Chronicles from Kashmir An Annotated, Multimedia Script - Dinesh, Nandita (Applied Theatre Praxis Series, 2020)
"'What is happening in Kashmir?' Chronicles from Kashmir explores this question through a site-adaptive 24-hour theatrical performance. Developed between 2013 and 2018 by the Ensemble Kashmir Theatre Akademi and Nandita Dinesh, the play uses a durational, promenade format to immerse its audience within a multitude of perspectives on life in Kashmir. From a wedding celebration that is interrupted by curfew, to schoolboys divided by policing strategies, and soldiers struggling with a toxic mixture of boredom and trauma, Chronicles from Kashmir uses performance, installation and collaborative creation to grapple with Kashmir's conflicts through the lenses of outsiders, insiders, and everyone in between. Due to varying degrees of censorship and suppression, the play has not been performed live since 2017. This book is, therefore, an attempt to keep Chronicles from Kashmir alive by including filmed scenes, a script, contextual questions, a glossary, and illuminating introductions by Nandita Dinesh and EKTA founder Bhawani Bashir Yasir. A valuable Open Access resource for practitioners, educators and students of performance and conflict, this book is also stimulating reading for anybody who has asked, 'What is happening in Kashmir?' This playscript includes: Twenty filmed scenes of the play in performance A range of contextual questions to stimulate discussion on staging site-adaptive theatre in places of conflict A helpful glossary"